Pengaruh Gaya Kepemimpinan dan Kompensasi Finansial pada Kepuasan Kerja dan Kinerja Karyawan di CV. Wali Sukses Mandiri - Oktaviani, Ni Made; Indrawati, Ayu Desi (E-Jurnal Manajemen, 2014)
ABSTRACT   The business world is increasingly showing the very tight competition. Therefore, aspects of performance and job satisfaction becomes a very important discussion. The final goal to be achieved is to provide solutions related to an increase in job satisfaction and employee performance. The study was conducted on the CV. Successful Independent trustee located in Gianyar, Bali. The population in this study amounted to 67 people. The sampling method used is the census so that the sample in this study amounted to 67 people. The analysis technique used is the path analysis. The results of the analysis of test paths and stated that the leadership style of each financial compensation has a positive effect on job satisfaction and employee performance and job satisfaction also has a positive effect on employee performance.
Keywords: Keywords: Leadership Style, Compensation, Job Satisfaction, Employee Performance